DESIGNING PROFESSIOGRAM OF THE HIGHER EDUCATIONAL ESTABLISHMENT LECTURER UNDER CONDITION OF CONTINUOUS PEDAGOGICAL EDUCATION - Вітченко, Андрій Олександрович (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article is devoted to scientific substantiation and designing the professiogram of the higher educational establishment lecturer under condition of continuous, competence-based pedagogical education. As a result of the theoretical methods application, the methodological guiding lines of the modern professiography have been identified, the diachronic aspects of the professiography requirements formation in the Ukrainian pedagogic have been highlighted, the theoretical views and approaches to the professiogram designing have been analyzed. On the basis of the modeled multilevel structure of the professiogram, the professiography requirements list in terms of the of the educational paradigm competence have been worked out, the conditions for their successful implementation in the system of continuous pedagogical education have been established. The most important recognized requirements are: the personal receptivity of the lecturer to innovations, the inevitable necessity for self-actualization and self-development, the self-worth awareness while implementation the educational purposes; focusing on achieving the positive results in pedagogical activities; the atmosphere of cooperation and co-creation in the academic environment, and so on. The conducted research proved the need for designing the professiogram of the higher educational establishment lecturer under condition of continuous pedagogical education based on the criteria of requirements in terms of the competence-based approach, clarifying the psychological and pedagogical conditions for its implementation